The detection of Mycobacterium tuberculosis using in vitro granuloma tuberculosis model intracelluler specimens - Imam Agus Faizal; Jusak Nugraha; Agung Dwi Wahyu Widodo (Department of D3 Medical Technology Laboratory STIKes Hutama Abdi Husada Tulungagung, 2020)
The Granulomas are a group of innate and adaptive immune cells that are highly organized, and during tuberculosis infection caused by the bacterium Mycobacterium tuberculosis. Estimated as many as 1.6 million cases of death in 2017 according to World Health Organization. Tuberculosis ranks in the top 10 causes of death worldwide and it is predicted that more than 1.7 billion people (around 25 percent of the world's population) are estimated to be infected by Mycobacterium tuberculosis. The purpose of this study was to confirm the Mtb by examining a new method by modifying Ziehl-Neelsen stain using an intracellular specimens for tuberculous granuloma in vitro. This study used the isolate of the bacterium Mycobacterium tuberculosis H37Rv obtained from the Microbiology Laboratory of the Institute of Tropical Disease Universitas Airlangga, Surabayaa, using Peripheral Blood Mononuclear Cells to make model granuloma tuberculosis. The result is Ziehl-Neelsen staining was modified, it was found that the Mycobacterium tuberculosis H37Rv as detection of bacterial confirmation is said to be successful.